Czasopismo jako tajemnica. Wariacje na temat czasu i pisma - Krajewska, Anna (Przestrzenie Teorii, 2022)
This editorial is an impressionistic work written on the occasion of the 20th anniversary of the journal “Przestrzenie Teorii” (“Spaces in Theory”), predominantly emphasising the history of the establishment and the nature of the journal associated with two universities – Adam Mickiewicz University in Poznań and the Jagiellonian University in Kraków. The jubilee issue is devoted to literature as a mystery